2017
DOI: 10.1371/journal.pone.0178546
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contaminants of honeybee products in Uganda detected using LC-MS/MS and GC-ECD

Abstract: Pollinator services and the development of beekeeping as a poverty alleviating tool have gained considerable focus in recent years in sub-Saharan Africa. An improved understanding of the pervasive environmental extent of agro-chemical contaminants is critical to the success of beekeeping development and the production of clean hive products. This study developed and validated a multi-residue method for screening 36 pesticides in honeybees, honey and beeswax using LC-MS/MS and GC-ECD. Of the 36 screened pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
(54 reference statements)
1
29
0
Order By: Relevance
“…The protocol was adapted from Amulen et al [25]. Separation was performed on a HP-5MS (5% phenyl methyl siloxane) capillary column (30 m × 0.25 mm, 0.25 μm).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was adapted from Amulen et al [25]. Separation was performed on a HP-5MS (5% phenyl methyl siloxane) capillary column (30 m × 0.25 mm, 0.25 μm).…”
Section: Methodsmentioning
confidence: 99%
“…Different scientific documents reported that pesticide residues(contamination) in honey, wax, bee brood, pollen, and bees in several countries (Chauzat et al 2006;Martel et al 2007;Frazier et al 2008;Mullin et al 2010;Wiest et al 2011;Ostiguy and Eitzer 2014;Porrini et al 2016;Amulen et al 2017;Valdovinos-Flores et al 2017).…”
Section: Pesticides Residues In Honeybee Productsmentioning
confidence: 99%
“…Multiple studies reporting the residue concentrations of pesticides in beehive products, mainly beeswax, honey and pollen, have been published in the last decade [6, 1020]. The majority of the studies, which surveyed beeswax and honey simultaneously from the same beehives, reported lower pesticide contamination of honey as compared with that of beeswax, in which pesticide concentrations occasionally reaching values of up to several dozens of mg/kg [1820]. Despite the yearly application of hundreds of approved pesticides in agricultural fields in Europe (e.g., 331 synthetic organic pesticides in 2016), only a small fraction of these active ingredients were actually screened in honey and beeswax samples (≤ 30%) in Europe [18–21].…”
Section: Introductionmentioning
confidence: 99%